SUBJECTIVE EXPERIENCE TO BE WIFE OF CONVICTED TERRORISM - Jayanti, Deti Anisa; Indrawati, Endang Sri (Empati, 2013)
This study aimed to describe the essence of subjective experience to be wife of convicted terrorism. Subjective experience to be wife of convicted terrorism is generally defined as a process how the wife of convicted terrorism life after her husband convicted as terrorist, what is experienced and felt and how her attitude for dealing various problems and social pressures.The study was conducted using a qualitative phenomenological approach . Subject of three people chosen by purposive sampling, Criteria of subject are subject is jihadists outside the conflict area’s wife and the husband has obtained court verdict for his involvement in the case of terrorism in Indonesia and his wife live in the same area as before the media revealed husband's case. The primary method of data collection was interview, audio material with supporting data and field notes . Data analysis refers to the model of Interpretative Phenomenological Analysis ( IPA ) .The results showed that wife deal with stressful situations caused by either psychological pressure from family and society and the problems that arise related to the wife's new role as a single mother. Subject reactions to stressful situations include cognitive, emotional, and behavioral. In terms of cognitive, three subjects experienced disorientation or confusion on toward the goal to decide something. While the emotional reaction to the subject in the early periods of stress showed a negative reaction as feeling hopeless, sad, and insecure. While the behavior, subjects tend to avoid things that make the subject uncomfortable and add to stressful situations. However, with positive reinterpretation, belief of God's help and social support are help the subject to deal with the stressor coping strategies were more dominant in problem focused coping . Reduced stress is also followed by a stronger belief in way of life chosen and the desire to keep and maintain a household with a husband who is still in jail.